Learning from health system reform trajectories in seven Canadian provinces. Issue 4 (6th October 2021) - Usher, Susan; Denis, Jean-Louis; Préval, Johanne; Baker, Ross; Chreim, Samia; Kreindler, Sara; Breton, Mylaine; Côté-Boileau, Élizabeth
Abstract: In publicly funded health systems, reform efforts have proliferated to adapt to increasingly complex demands. In Canada, prior research (Lazar et al ., 2013, Paradigm Freeze: Why is it so Hard to Reform Health Care in Canada?, McGill-Queen's Press) found that reforms at the end of the 20th century failed to change the fundamentals of the Canadian system based on physician independence and assured universal coverage only for medical and hospital services. This paper focuses on reforms since the turn of the millennium to explore the transformative capacities developed in seven provinces within this system architecture. Longitudinal case studies, based on scientific and grey literature, and interviews with key informants, trace the patterns of reform in each province and reveal five objectives that, to varying degrees, preoccupied reformers: (1) address chronic disease, (2) align health system actors with provincial objectives, (3) shift from hospital to community-based care, (4) integrate physicians, and (5) develop improvement capacities. The range of strategies adopted to achieve these objectives in different provinces is compared to identify emerging pathways of reform and extract lessons for future reformers. We find significant cross-learning between provinces, but also note an emergent dimension to reforms, where multiple strategies aggregate through time to create unique patterns, presenting their own set of possibilities and limitations for the future.